The Impact of Climate in Inclusive Classrooms - Influencing the Motivation of Students with Special Needs - Duka, Ambera; Leka, Klodiana; Vampa, Magdalini; Bursová , Janka; Jenisová , Zita (Journal of Education Culture and Society, 2024)
Aim: The study aims to analyze the climate factors in inclusive classes in motivating students with special needs to increase their academic achievements and improve social behaviors. Through a qualitative methodology, the study investigated several dimensions of supportive and open classroom climate on their impact on the performance of students with special needs in inclusive classrooms. Through the suggestions that this study offers, the close relationship that the supportive climate has in the motivation of students in the classroom, especially when different techniques of group activities are developed can be easily seen. Method: For the realization of this study, ninety-two (92) students/teachers of the "Teachers in Primary Education" program of the second cycle of studies at "Aleksander Moisiu" University in Durres were included and were divided into four (4) focus groups. At the same time, semi-structured interviews were conducted with twenty-one (21) primary education teachers (grades 1-5) in three schools in the Municipality of Durres.Results: The findings of the study highlight that collaborative climate factors in inclusive classrooms influence and motivate students with special needs. Several issues related to students' motivation have been identified, specifically: their motivation increases during group work, their motivation increases in project-based learning, and their motivation increases in the reinforcement of hard skills they bring to teaching supported by ICT. Conclusion: Students and teachers also reported that all these beliefs and attitudes directly affect the performance of students with special needs and therefore their achievements. Teachers emphasize that students with special needs are more involved in group work, and some of the benefits that students with special needs have, are: improved communication and interaction by strengthening cooperation and self-efficacy. On the other hand, some of the benefits of project work that parents highlighted are: that children become more social; lasting friendships develop; self-esteem increases; and everyone's values and abilities stand out.